THE IMPORTANCE OF ENVIRONMENTAL EDUCATION IN THE SCHOOL CONTEXT IN AMAZONAS: A CASE STUDY FROM TEACHERS’ PERCEPTION - Bittencourt Saraiva, Waslany (Revista Gênero e Interdisciplinaridade, 2023)
The topic of the importance of environmental education in the school context in Amazonas will be presented, the research objective of which was to verify, based on the perception of teachers, whether environmental education projects and actions in schools in Amazonas bring significant results that translate into personal practices in students’ daily lives, as well as identifying whether reflections and changes in attitudes regarding environmental issues occur in students’ daily lives, their level of interest in environmental issues and what to do to resolve them; in addition to verifying the environmental actions carried out by schools. The research was carried out with ten teachers from several municipalities in Amazonas, including the municipalities of Manaus, Altazes, Presidente Figueiredo, Urucurituba, Codajás, Novo Airão and Beruri, chosen randomly among doctoral students from the Doctorate in Education Sciences course at the University of Del. Sun - Paraguay. Environmental education in the educational environment helps teachers and students expand their way of thinking and acting in an integrative way in the face of complex global problems.